Cutaneous vasculitis and immune complexes in severe bronchiectasis. Issue 3 (March 1984) - Hilton, A M; Hasleton, P S; Bradlow, A; Leahy, B C; Cooper, K M; Moore, M
Abstract : Four patients with severe bronchiectasis (chronic bronchial suppuration) are described who developed cutaneous lesions associated with exacerbations of their respiratory disease. The skin abnormalities consisted of purpuric lesions in three patients and an erythematous vasculitis in one. Circulating immune complexes were present in all patients and in three skin biopsy specimens showed deposition of C3, IgG, and IgA in dermal blood vessels. Haemophilus influenzae had been isolated from the sputum of all four patients and in two patients was present at the time the cutaneous lesions appeared. It is suggested that local immune complex deposition was responsible for the skin lesions which occurred during acute exacerbations of bronchiectasis.